Bioprospecting with Reference to Medicinal Insects and Tribes in India : an Overview - Senthilkumar, N.; Barthakur, Nizara D.; Lokeshwara Rao, M. (Indian Forester, 2008)
Entomophagy (i.e. use of insects as food) is practiced in many parts of the world including India but the use of insects, as medicine is done in very few parts of the world and we are fortunate that North-East people of India are rich in this traditional medicinal knowledge. Tribes of North-East India have been using several insect based traditional drugs to cure several diseases. Over 500 species of insects are used as medicine to cure common ailments to complicated ailments in the North-East from time immemorial. Some valuable information regarding traditional medicinal uses of common insects by folk doctors has been summarised.